Systematic Literature Riview: Model Pembelajaran Search, Solve, Create and Share untuk Pembelajaran Matematika - Via Oktaviana; As Elly; Yufitri Yanto (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This paper presents a Systematic Literature Review (SLR) on the implementation of the Search, Solve, Create, and Share (SSCS) learning model in mathematics learning. This investigation employed the PRISMA protocol to systematically identify, evaluate, and analyze pertinent studies. Articles were collected from Google Scholar, Garuda, and SciSpace databases using the keywords “SSCS”, “Search Solve Create and Share”, and “SSCS learning model”. The inclusion criteria included national and international articles discussing the SSCS model in mathematics learning published between 2017–2026, available in full text, and relevant to the research focus. Based on the selection process, 12 articles were analyzed using a qualitative descriptive approach. The results showed that the SSCS learning model has a positive effect on students’ mathematics learning outcomes, problem-solving abilities, critical thinking, reflective thinking, conceptual understanding, mathematical disposition, and self-efficacy. In addition, the SSCS model encourages active student participation through the stages of Search, Solve, Create, and Share. However, this model requires more learning time and depends on students’ activeness during the learning process. Therefore, the SSCS model can be used as an innovative alternative learning model in mathematics education.